In-vitro antioxidant activity and phytochemical analysis in extracts of Hibiscus rosa-sinensis stem and leaves - Garg, Deepa; Shaikh, Ayesha; Muley, Aditya; Marar, Thankamani (Free Radicals and Antioxidants)
Free radicals induce numerous diseases by lipid peroxidation, and DNA damage. It has been reported that numerous plant extracts have antioxidant activities to scavenge free radicals. In the present study, the antioxidant properties of crude (aqueous and methanolic) extract of Hibiscus rosa sinensis (Malvaceae) were studied in six in vitro models viz. radical scavenging activity by DPPH reduction Assay, Scavenging of SO, H2O2 and NO, reducing power, FRAP assay. The extract was found to contain large amounts of phenolic compounds and flavonoids. Methanolic extract of Hibiscus rosa-sinensis possessed significant antioxidant activity as compare to aqueous extract. These results suggest that hibiscus has potential to develop a new functional dietary agent to treat chronic metabolic diseases, such as diabetes and hyperlipidemia.
Keywords: Hibiscus rosa-sinensis; antioxidant capacity; scavenging activity; in-vitro models